2019
DOI: 10.1542/peds.2018-3117
|View full text |Cite
|
Sign up to set email alerts
|

Safety Interventions and Liquid Laundry Detergent Packet Exposures

Abstract: OBJECTIVES: To investigate exposures to liquid laundry detergent packets among children <6 years old in the United States and to evaluate the impact of the American Society for Testing and Materials voluntary product safety standard. METHODS: Data from the National Poison Data System involving exposures to liquid laundry detergent packets from 2012 to 2017 were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…A more recent study also evaluated changes in counts of accidental LLP exposures reported to NPDS and showed modest decreases in the number of exposures in children <6 years old [31]. Gaw et al found decreases in exposures, HCF use, HCF admission, and serious outcomes in children <6 years old, but also reported increased exposures in older children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study also evaluated changes in counts of accidental LLP exposures reported to NPDS and showed modest decreases in the number of exposures in children <6 years old [31]. Gaw et al found decreases in exposures, HCF use, HCF admission, and serious outcomes in children <6 years old, but also reported increased exposures in older children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, these pods present potential toxic safety hazards to young children and adolescents as they contain concentrated detergent enveloped in a watersoluble membrane. 1,2 In their article, Gaw et al 3 indicate that from 2012 to 2017 there were 72,947 single and polysubstance exposures to liquid laundry detergent packets reported in the National Poison Data System:…”
mentioning
confidence: 99%
“…Young children are often disproportionately represented among these exposures because of their exploratory behaviors and their attraction to the toy-and candy-like appearance of many detergent packets. 3 The industry has responded with measures to decrease the "attractiveness" of the pods, and when children do handle them, childproofing measures have been instituted with a quantifiable decrease in ingestions from 2015 to 2017. 3 However, despite these interventions, exposures continue to occur with an increase in children age 7 to 17 years.…”
mentioning
confidence: 99%
See 2 more Smart Citations